THE EVOLUTION OF TRANSLATION THEORY AND ITS METHODOLOGICAL APPLICATIONS: FROM HISTORICAL FOUNDATIONS TO CONTEMPORARY PROBLEMS OF EQUIVALENCE, CULTURE, AND PRACTICE - Abdullaeva Rushana Shukhrat kizi,; Kholmurodova Ugiloy Nurullo kizi, (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Abstract: This article examines the evolution of translation theory from its historical roots to contemporary approaches, highlighting its methodological applications in modern practice. It analyzes the development of equivalence, the impact of cultural context, and the challenges that translators face in practical translation settings. The study emphasizes the role of translation theory in providing a structured framework for translation strategies, ensuring accurate and culturally appropriate communication. Contemporary translation theory integrates linguistic, cultural, and pragmatic aspects, offering solutions to complex translation problems in various fields such as literary, technical, and digital communication. The article also discusses the relevance of methodological approaches for training translators and enhancing translation quality.